Reviews of Physiology, Biochemistry and Pharmacology
DOI: 10.1007/s10254-003-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 and Hsp90—a relay team for protein folding

Abstract: Molecular chaperones are a functionally defined set of proteins which assist the structure formation of proteins in vivo. Without certain protective mechanisms, such as binding nascent polypeptide chains by molecular chaperones, cellular protein concentrations would lead to misfolding and aggregation. In the mammalian system, the molecular chaperones Hsp70 and Hsp90 are involved in the folding and maturation of key regulatory proteins, like steroid hormone receptors, transcription factors, and kinases, some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
496
0
32

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 567 publications
(540 citation statements)
references
References 409 publications
(339 reference statements)
12
496
0
32
Order By: Relevance
“…6). This result corroborates that the cation plays a role in mediating contacts between Hsp70 and nucleotide [56,57].…”
Section: Nucleotide-induced Stability Changessupporting
confidence: 83%
“…6). This result corroborates that the cation plays a role in mediating contacts between Hsp70 and nucleotide [56,57].…”
Section: Nucleotide-induced Stability Changessupporting
confidence: 83%
“…Analysis by semi-quantitative methods at the mRNA level by Northern blot or at the protein level by Western blot clearly demonstrated complex regulation. Furthermore, more recent evidence showed that HSPs are involved in the cell response to most environmental and physiological stressors (reviewed by Wegele et al 2004). This includes studies in molluscs (CruzRodriguez et al 2000;Snyder et al 2001;Boutet et al 2003;Piano et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Hop optimises the functional cooperation between Hsp70 and Hsp90 which requires highly co-ordinated interactions for the folding and conformational regulation of a variety of proteins [5]. The molecular chaperone complex of Hop, Hsp70 and Hsp90 is involved in the folding and maturation of key regulatory proteins involved in cell viability [6], such as steroid hormone receptors, transcription factors and kinases (some of which are involved in cancer progression). The role of Hop in tumour progression is not fully elucidated; however, Hop has been shown to be over expressed in colonic carcinoma cells [7] and in hepatocellular carcinoma (HCC) [8].…”
Section: Introductionmentioning
confidence: 99%